Evaluation of Setting Time, Flowability, Film Thickness, and Radiopacity of Experimental Monocalcium Silicate-Based Root Canal Sealers - Sukanya Juntha; Pakit Tungsawat; Ninnita Wongwatanasanti; Warattama Suksaphar; Siripat Lertnantapanya (Hindawi Limited, 2024)
Introduction. This study aimed to evaluate the efficacy of a formulation of premixed calcium silicate-based sealer (CSBS) with monocalcium silicate (Mono-CS) as the main component. Its properties were compared with those of a control group (iRoot SP) according to ISO 6876/2012 standards for root canal sealers. Materials and Methods. The CSBS formulation consisted of two components (powder and liquid). The powder was a mixture of Mono-CS, a radiopacifier, and a thickening agent, and the liquid components were nonaqueous liquid agent and setting accelerator. Three formulation groups with different powder-liquid ratios were prepared: group A, 2 : 1; group B, 3 : 1; and group C, 2 : 1, which also contained calcium chloride as a setting accelerator. The setting time, flow rate, film thickness, and radiopacity of the three CSBS groups and the control group were evaluated and compared. Each test was repeated five times for each group. Results. The minimum values of setting time (i.e., working time, initial setting time, and final setting time) were ranked in order of significance as group B, the control group, group C, and group A. The control group had the lowest film thickness at 20 μm, with a nonsignificant difference to group C. The flow rates in group A, group C, and the control group were >20 mm. Furthermore, the experimental groups showed a similar amount of radiopacity as the control group (p >0.05). Conclusion. Mono-CS and calcium chloride can be used in the formulation of root canal sealers, and their properties, including working time, initial setting time, final setting time, flow rate, film thickness, and radiopacity, are consistent with those of iRoot SP and ISO 6876/2012 standards.